Konflik Kepala Daerah: Strategi Pencegahan dan Penyelesaian - Kelik Iswandi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
The Local Chief Executive and Vice elections in Indonesia are conducted together, which leads to potential conflicts in the relationship between both parties. Therefore, this research aimed to examine the causes and mechanisms for resolving conflicts between Local Chief Executive and Vice. This is empirical juridical research with the primary, secondary, and tertiary data analyzed through the utilization of a statutory and conceptual approach. The results showed that the conflict between the Local Chief Executive and the Vice was caused by the absence of chemistry and a clear division of duties. The two alternative mechanisms that can be used to prevent the conflict are mate selection during the nomination period, and the application of an agreement mechanism in accordance with the laws and political agreements. Vertical settlement mechanism, which enables the Local House of Representative (DPRD) was adopted to resolve persistent conflict in accordance with the controlling function. This mechanism is a new concept that can be used as a guideline for resolving Local Chief Executive conflicts in Indonesia.